2007
DOI: 10.1124/mol.107.042002
|View full text |Cite
|
Sign up to set email alerts
|

Antitumorigenic Effects of Peroxisome Proliferator-Activated Receptor-γ in Non-Small-Cell Lung Cancer Cells Are Mediated by Suppression of Cyclooxygenase-2 via Inhibition of Nuclear Factor-κB

Abstract: Pharmacological activators of peroxisome proliferator-activated receptor-␥ (PPAR␥) inhibit growth of non-small-cell lung cancer (NSCLC) cell lines in vitro and in xenograft models. Because these agents engage off-target pathways, we have assessed the effects of PPAR␥ by overexpressing the protein in NSCLC cells. We reported previously that increased PPAR␥ inhibits transformed growth and invasiveness and promotes epithelial differentiation in a panel of NSCLC expressing oncogenic K-Ras. These cells express high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
54
1
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 36 publications
6
54
1
1
Order By: Relevance
“…Also, ciglitazone suppressed COX-2 mRNA expression and COX-2 promoter activity, while upregulating peroxisome proliferator response element promoter activity in NSCLC cells further suggesting a negative modulator role for PPARγ ligands on the COX-2/PGE2 pathway in NSCLC [63] . Of note, in vitro studies and xenograft models have demonstrated that elevated COX-2 expression is critical for promoting lung tumorigenesis, and that the anti-tumorigenic effects of PPARγ ligands are mediated through suppression of COX-2 via increased activity of PTEN, decreased levels of phospho-Akt, and inhibition of nuclear factor-kB (NF-kB) activity [64] .…”
Section: Pparγ Ligands and Cyclooxygenase-2-related Pathwaysmentioning
confidence: 99%
“…Also, ciglitazone suppressed COX-2 mRNA expression and COX-2 promoter activity, while upregulating peroxisome proliferator response element promoter activity in NSCLC cells further suggesting a negative modulator role for PPARγ ligands on the COX-2/PGE2 pathway in NSCLC [63] . Of note, in vitro studies and xenograft models have demonstrated that elevated COX-2 expression is critical for promoting lung tumorigenesis, and that the anti-tumorigenic effects of PPARγ ligands are mediated through suppression of COX-2 via increased activity of PTEN, decreased levels of phospho-Akt, and inhibition of nuclear factor-kB (NF-kB) activity [64] .…”
Section: Pparγ Ligands and Cyclooxygenase-2-related Pathwaysmentioning
confidence: 99%
“…NF-kB activation was determined as previously described 43 with modifications. Briefly, HK-2 cells were grown to 50% confluence in six-well plates and transiently transfected with a NF-kB luciferase reporter cassette and a b-galactosidase reporter (used for normalizing the transfection efficiency).…”
Section: Nf-kb Activity Assay In Cultured Cellsmentioning
confidence: 99%
“…COXs catalyze the oxidative metabolism of arachidonic acid into prostaglandin H2, which is the precursor of other prostaglandins including prostaglandin G2 (PEG2) [48,49]. PEG2 has been reported to inhibit Fas-induced apoptosis and markedly increase expression of Mcl-1 in KMBC cholangiocarcinoma cells [50].…”
Section: Discussionmentioning
confidence: 99%